Finding Business Opportunities and Business Strategy from Islamic Society Culture - Marasabessy , Andi (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
This research was conducted to find out how to find business opportunities and business strategies from the existence of community culture. This study uses a qualitative research approach. The study was conducted on the island of Haruku, Central Maluku, Eastern Indonesia. The results of the study show that culture provides opportunities for the creation of several types of businesses on the island of Haruku. Other results show that culture becomes a strategy in business. The results of the research contribute to management science, especially regarding environmental management due to the community culture. The results of this study are recommended to be developed using action research methods or quantitative research methods.